THE INFLUENCE OF SYSTEM QUALITY AND INFORMATION QUALITY ON STUDENT SATISFACTION IN BUSINESS ADMINISTRATION DEPARTMENT USING THE EMIS APPLICATION AT THE STATE POLYTECHNIC OF KUPANG - Hamzah Nazarudin; Hendrik Toda; Melkisedek N B C Neolaka; Maria L Lino (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This study aims to determine the effect of system quality and information quality on student satisfaction in using the Educational Management Information System (EMIS) application at Kupang State Polytechnic. This study was motivated by various obstacles in using the EMIS application, such as slow system access, disruptions during course registration (KRS), and inconsistencies and delays in updating academic information that affect the level of student satisfaction. This study uses a quantitative approach using a survey method. The sampling technique uses probability sampling with a random sampling method. The sample consisted of 175 respondents who were students of the Business Administration Department of Kupang State Polytechnic. Data analysis was carried out using multiple linear regression analysis with the help of the SPSS program. The results showed that system quality has a positive effect on student satisfaction, with a t-value of 3.207 and a significance level of 0.002 <0.05. Information quality also has a positive effect on student satisfaction, with a t-value of 7.328 and a significance level of 0.000 <0.05. Simultaneously, system quality and information quality have a positive effect on student satisfaction, with an F value of 7.883 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) value of 0.505 indicates that 50.5% of student satisfaction can be explained by system quality and information quality, while the remaining percentage is influenced by other variables outside this study. This study concludes that system quality and information quality are important factors in increasing student satisfaction with the use of the EMIS application. Therefore, system administrators are expected to improve system stability, access speed, data security, and the quality of academic information in real time to support effective and efficient digital-based academic services.